Prevalence of sleep‐disordered breathing in a multiethnic Asian population in Singapore: A community‐based study. Issue 5 (29th February 2016) - Tan, Adeline; Cheung, Yan Yi; Yin, Jason; Lim, Wei‐Yen; Tan, Linda W.L.; Lee, Chi‐Hang
Abstract: Background and objective: Limited data exist on the prevalence variation in sleep‐disordered breathing (SDB) across different Asian ethnicities. This population study aimed to estimate the prevalence of SDB in Singapore, a multiethnic nation, and to quantify the prevalence variation among Chinese, Malays and Indians. Methods: The Singapore Health Study 2012 was a cross‐sectional population study conducted on adults aged 21–79 years. Among 2329 participants who completed baseline examination, a sample of 242 subjects completed home‐based sleep testing with an Embletta device (type 3 monitor). Moderate‐to‐severe SDB, defined as an apnoea–hypopnoea index (AHI) of ≥15 events/h, was used to estimate prevalence. Results: The weighted estimates of the population prevalence of moderate‐to‐severe SDB and sleep apnoea syndrome were 30.5% and 18.1%, respectively. Of subjects with AHI ≥15, 91.0% were previously undiagnosed. Moderate‐to‐severe SDB prevalence varied across the Chinese (32.1%), Malays (33.8%) and Indians (16.5%). The mean body mass index (BMI) was lowest in Chinese (23.3 kg/m 2 ) and highest among Malays (26.0 kg/m 2 ) and Indians (25.4 kg/m 2 ). Compared with Chinese, Indians had lower odds of moderate‐to‐severe SDB after adjustment for age, sex and BMI (odds ratio 0.82, 95% CI: 0.70–0.96, P = 0.02). Conclusion: Sleep‐disordered breathing is prevalent but mostly undiagnosed among Asians in Singapore. There was a lower prevalence of SDB among Indians compared with Chinese that remained after adjustment for age, sex and BMI. Strategies are needed to optimize diagnosis and recognize ethnic differences in SDB prevalence. Abstract : We found an estimated population prevalence of moderate‐severe SDB of 30.5% in Singapore. Ninety‐one percent of subjects with moderate‐to‐severe SDB were previously undiagnosed. Moderate‐to‐severe SDB prevalence varied across Chinese, Malay and Indian people. Indian people had lower odds of moderate‐to‐severe SDB compared to Chinese people after adjustment for BMI, age and sex.